Quantitative Detection of Active Vibrios Associated with White Plague Disease in Mussismilia braziliensis Corals - Chimetto Tonon, Luciane A.; Thompson, Janelle R.; Moreira, Ana P. B.; Garcia, Gizele D.; Penn, Kevin; Lim, Rachelle; Berlinck, Roberto G. S.; Thompson, Cristiane C.; Thompson, Fabiano L. (Frontiers in Microbiology, 2017)
Over recent decades several coral diseases have been reported as a significant threat to coral reef ecosystems causing the decline of corals cover and diversity around the world. The development of techniques that improve the ability to detect and quantify microbial agents involved in coral disease will aid in the elucidation of disease cause, facilitating coral disease detection and diagnosis, identification and pathogen monitoring, pathogen sources, vectors, and reservoirs. The genus Vibrio is known to harbor pathogenic strains to marine organisms. One of the best-characterized coral pathogens is V. coralliilyticus, an aetilogic agent of White Plague Disease (WPD). We used Mussismilia coral tissue (healthy and diseased specimens) to develop a rapid reproducible detection system for vibrios based on RT-QPCR and SYBR chemistry. We were able to detect total vibrios in expressed RNA targeting the 16S rRNA gene at 5.23 x 106 copies/ug RNA and V. coralliilyticus targeting the pyrH gene at 5.10 x 103 copies/ug RNA in coral tissue. Detection of V. coralliilyticus in diseased and in healthy samples suggests that white plague disease (WPD) in the Abrolhos Bank may be caused by a consortium of microorganism and not only a single pathogen. We developed a more practical and economic system compared with probe uses for the real-time detection and quantification of vibrios from coral tissues by using the 16S rRNA and pyrH gene. This qPCR assay is a reliable tool for the monitoring of coral pathogens, and can be useful to prevent, control, or reduce impacts in this ecosystem.